2011
DOI: 10.1016/j.baae.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Robustness to secondary extinctions: Comparing trait-based sequential deletions in static and dynamic food webs

Abstract: Number of words in manuscript: 6768Number of words in abstract: 260 Number of words in title:14 Curtsdotter et al. Basic and Applied Ecology 2 AbstractThe loss of species from ecological communities can unleash a cascade of secondary extinctions, the risk and extent of which are likely to depend on the traits of the species that are lost from the community. To identify species traits that have the greatest impact on food web robustness to species loss we here subject allometrically scaled, dynamical food web m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(147 citation statements)
references
References 45 publications
8
138
1
Order By: Relevance
“…The loss of large-bodied populations in food websas may result from warming [73,74]-may cause secondary-extinction avalanches [72,77,78]. Climate change may thus induce trophic cascades where the loss of species (in particular large ones) has alternating positive and negative effects on the trophic levels below (figure 2).…”
Section: Warming and Top-down Controlmentioning
confidence: 99%
“…The loss of large-bodied populations in food websas may result from warming [73,74]-may cause secondary-extinction avalanches [72,77,78]. Climate change may thus induce trophic cascades where the loss of species (in particular large ones) has alternating positive and negative effects on the trophic levels below (figure 2).…”
Section: Warming and Top-down Controlmentioning
confidence: 99%
“…This model has been extensively used to derive theory based on numerical simulations (e.g. Binzer et al 2011;Curtsdotter et al 2011;Berlow et al 2009;Brose et al 2006). Recently, this framework has also been extended to mechanistically model the effect of temperature on community dynamics (Gilbert et al 2014;Vasseur et al 2005;O'Connor et al 2011), using metabolic theory of ecology (Brown et al 2004).…”
Section: Species Interactions and Community Dynamicsmentioning
confidence: 99%
“…Curtsdotter et al 2011;Ebenman et al 2004;Berlow et al 2009). In a food web context, the topological approach only captures bottom up effects (species losing all their prey will go extinct), whereas the dynamical approach can reveal both bottom-up and top-down effects (Eklöf and Ebenman 2006;Curtsdotter et al 2011). When it comes to less severe perturbations some research has focused on community sensitivity analysis (Berg et al 2011).…”
Section: Time Series Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Population growth rate is one factor that can cause differences in species' environmental response within food webs [12]. Additionally, multiple studies on food web models have revealed the potential for both large [13,14] as well as small [15] changes in species' densities or structural changes [16,17] to give cascading effects on other positions in the food web. The combined effect from environmental variation and species -species interactions is likely complex but nevertheless utterly important to disentangle.…”
Section: Introductionmentioning
confidence: 99%